Genotoxicity of 2,6- and 3,5-Dimethylaniline in Cultured Mammalian Cells: The Role of Reactive Oxygen Species - Chao, Ming-Wei (Oxford University Press, 2012)
Several alkylanilines with structures more complex than toluidines have been associated epidemiologically with human cancer. Their mechanism of action remains largely undetermined, and there is no reported evidence that it replicates that of multicyclic aromatic amines even though the principal metabolic pathways of P450-mediated hydroxylation and phase II conjugation are very similar. As a means to elucidate their mechanisms of action, lethality and mutagenicity in the adenine phosphoribosyltransferase (aprt (+/−)) gene induced in several Chinese hamster ovary cell types by 2,6- and 3,5-dimethylaniline (2,6-DMA, 3,5-DMA) and their N- and ring-hydroxyl derivatives (N-OH-2,6-DMA, N-OH-3,5-DMA, 2,6-DMAP, 3,5-DMAP) were assessed. Dose-response relationships were determined in the parental AA8 cell line, its repair-deficient UV5 subclone and other repair-deficient 5P3NAT2 or -proficient 5P3NAT2R9 subclones engineered to express mouse cytochrome P4501A2 (CYP1A2) and human N-acetyltransferase (NAT2), and also in AS52 cells harboring the bacterial guanine-hypoxanthine phosphoribosyltransferase (gpt) gene. Mutations in the gpt gene of AS52 cells were characterized and found to be dominated by G:C to A:T and A:T to G:C transitions. Separately, treatment of AS52 cells with N-OH-2,6-DMA, N-OH-3,5-DMA, 2,6-DMAP, 3,5-DMAP, and 3,5-DMAP led to intracellular production of reactive oxygen species (ROS) for at least 24h after removal of the mutagens in every case. Using the comet assay, DNA strand breaks were observed in a dose-dependent manner in AS52 cells when treated with each of the four N-OH-2,6-DMA, N-OH-3,5-DMA, 2,6-DMAP, and 3,5-DMAP derivatives. Comparative evaluation of the results indicates that the principal mechanism of mutagenic action is likely to be through redox cycling of intracellularly bound aminophenol/quinone imine structures to generate ROS rather than through formation of covalent DNA adducts.